Structural and magnetic studies of TiO2 rutile implanted with vanadium ions - OKAY, CENGİZ (IOP PUBLISHING LTD, 2019)
Single crystal (100) and (001) TiO2 rutile plates were implanted with vanadium 40 keV ions to the fluence of 1.5 x 10(17) ion cm(-2). A set of samples was also annealed at high-temperature in air to restore oxygen stoichiometric content and recover the TiO2 lattice structure after the high-dose ion implantation. In addition, a control set of TiO2 rutile plates was implanted with 40 keV argon ions to the same fluence to explore the effect of radiation-induced defects on magnetic properties. Rutherford backscattering spectroscopy (RBS), x-ray photoelectron spectroscopy (XPS) and vibrating sample magnetometry (VSM) measurements were carried out to characterize the structural and magnetic properties of the vanadium-implanted TiO2. Both as-implanted and subsequently annealed V-TiO2 samples reveal ferromagnetic response at room temperature. Strong ferromagnetism observed in the vanadium-implanted (001) TiO2 plates is related to the \substitutional V4+ ions coupled by the indirect exchange via electrons trapped at oxygen vacancies, while much weaker ferromagnetism in the (100)oriented plates and the Ar-implanted samples is attributed to lattice defects induced by the high-dose ion irradiation. Suppression of the ferromagnetic response in the vanadium-implanted (001) TiO2 after the thermal treatment is explained by filling in the oxygen vacancies due to oxygen diffusion during annealing in air atmosphere.
Keywords: titanium dioxide; ion-beam implantation; vanadium ions; radiation defects; ferromagnetism; diluted magnetic oxides; ROOM-TEMPERATURE FERROMAGNETISM; V-DOPED TIO2; SINGLE-CRYSTALS; DEFECTS; STATES; FILMS